Rhabdomyosarcoma of the cervix in teenagers - Is fertility preservation a feasible option? - F.E. Buruiana; B. Gupta; K. Singh (Elsevier, 2020)
Embryonal rhabdomyosarcoma (RMS) of the cervix is a rare entity, encountered mainly in the first two decades of life. The literature consists mainly of case reports and few small case series, and no standard treatment guidelines are available. As this is a disease of adolescence, fertility preservation in well selected cases is of paramount importance. We report 3 cases of cervical RMS, in adolescents highlighting the clinical presentation, diagnosis and management.